Optimal Outage Management Model Considering Emergency Demand Response Programs for a Smart Distribution System - Sobhan Dorahaki; Rahman Dashti; Hamid Reza Shaker (Applied Sciences, 2020)
In this paper, a novel smart outage management system considering Emergency Demand Response Programs (EDRPs) and Distributed Generations (DGs) denoted as <semantics>SOM<msubsup>SDGsEDRPs</msubsup></semantics> is proposed. The EDRPs are provided to decrease the cost of load shading in a time of emergency. The objective function of the problem is proposed to minimize the load shading cost, the DG dispatch cost, the demand response cost and the repair dispatch time for crews. The <semantics>SOM<msubsup>SDGsDERPs</msubsup></semantics> solves an optimization problem that is formulated as Mixed Integer Linear Programming (MILP) taking into account the grid topology constraints, EDRP constraints, DG constraints and crew constraints. The MILP formulation was demonstrated in the GAMS software and solved with the CPLEX solver. The proposed method was tested on the IEEE 34 bus test system as well as an actual Iranian 66 bus power distribution feeder. The results show that the EDRPs and DGs can be effective in decreasing the outage cost and increasing the served load of the distribution power system in a crisis time.